2008
DOI: 10.1073/pnas.0711527105
|View full text |Cite
|
Sign up to set email alerts
|

Capillarity-like growth of protein folding nuclei

Abstract: A full structural description of transition state ensembles in protein folding includes the specificity of the ordered residues composing the folding nucleus as well as spatial density. To our knowledge, the spatial properties of the folding nucleus and interface of specific nuclei have yet to receive significant attention. We analyze folding routes predicted by a variational model in terms of a generalized formalism of the capillarity scaling theory that assumes the volume of the folded core of the nucleus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Recently, a similar approach was applied for the TPR family, where increasing the stability of the interface between its repeats changed the folding from a multistate mechanism to a two-state one (32). In particular, a simple folding theory based on the capillarity model for propagating the linear protein (57)(58)(59) is in very good agreement with the simulation results. This simple model predicts that the folding rate of a protein with n repeating units is controlled by the energetics of the interface, and that its stability is determined by the ratio between the inter-and intrarepeat stabilities.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, a similar approach was applied for the TPR family, where increasing the stability of the interface between its repeats changed the folding from a multistate mechanism to a two-state one (32). In particular, a simple folding theory based on the capillarity model for propagating the linear protein (57)(58)(59) is in very good agreement with the simulation results. This simple model predicts that the folding rate of a protein with n repeating units is controlled by the energetics of the interface, and that its stability is determined by the ratio between the inter-and intrarepeat stabilities.…”
Section: Discussionmentioning
confidence: 68%
“…As stated earlier, the naturally occurring heterodimeric monellin can be thought of as two disordered proteins that fold upon binding. In our simulations, the β2-β3 interactions form before the transition state, and thus most of the interchain interface is the folding nucleus . Furthermore, deleting these β2-β3 interactions suppresses structure formation in both “chains” of scMn.…”
Section: Discussionmentioning
confidence: 72%
“…In our simulations, the β2-β3 interactions form before the transition state, and thus most of the interchain interface is the folding nucleus. 55 Furthermore, deleting these β2-β3 interactions suppresses structure formation in both "chains" of scMn. We conclude that having a folding nucleus that spans the two chains keeps them disordered until they encounter each other.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The theoretical framework of this model was first introduced by Portman et al (13)(14)(15) for the study of the protein folding problem, which demonstrated its usefulness in constructing the free energy surface of globular proteins (13)(14)(15)(16)(17). Later, Qi and Portman (18) implemented the model in the calculation of protein folding rates and the classification of folding patterns of two-state proteins (19). The essence of the variational model is to determine the folding pathway from unfolded to folded states by varying the constraints on each residue from small to large number, continuously.…”
Section: Introductionmentioning
confidence: 99%